PCDH7 Inhibits the Formation of Homotypic Cell-in-Cell Structure - Wang, Chenxi; Chen, Ang; Ruan, Banzhan; Niu, Zubiao; Su, Yan; Qin, Hongquan; Zheng, You; Zhang, Bo; Gao, Lihua; Chen, Zhaolie; Huang, Hongyan; Wang, Xiaoning; et al. (Frontiers in Cell and Developmental Biology, 2020)
Though homotypic cell-in-cell (hoCIC) structures are implicated in the development and progression of multiple human tumors, the molecular mechanisms underlying their formation remain poorly understood. We found that the expression of Protocadherin-7 (PCDH7), an integral membrane protein, was negatively associated with the formation of hoCIC structures. Overexpression of PCDH7 efficiently inhibits, while its depletion significantly enhances, hoCIC formation, which was attributed to its regulation on intercellular adhesion and contractile actomyosin as well. Via directly interacting with and inactivating PP1α, a protein phosphatase that dephosphorylates pMLC2, PCDH7 increases the level of pMLC2 leading to enhanced actomyosin at the intercellular region and compromised hoCIC formation. Remarkably, PCDH7 enhanced anchorage-independent tumor growth in a hoCIC-dependent manner. Together, we identified PCDH7 as the first trans-membrane protein that inhibits hoCIC formation to promote tumor growth.